BLOOD-GROUP ABO AND RHESUS FACTOR SYSTEMS DISTRIBUTION IN INDIVIDUALS OF VIETNAMESE NATIONALITY: BLOOD-GROUP ABO AND RHESUS FACTOR SYSTEMS DISTRIBUTION IN INDIVIDUALS OF VIETNAMESE NATIONALITY - Todorov, Velislav; Boycheva, Maria; Minkov, Cvetan; Georgiev, Volodia; Boichev, Milen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article reports the results of a study of blood group ABO and Rhesus factor systems conducted on 423 Vietnamese citizens (104 men and 319 women) aged 19 to 77 who lived or are currently living in Bulgaria. The frequency of the individual groups of the AB0 system is: 0 - 49,88%, B - 25,06%, A - 21,75%, AB - 3,31%, and the gene frequency - r = 0,711, q = 0,155, p = 0.134. Only subsets A1 and A1B were detected in the ABO system. There was only Rh in the studied population.